An evaluation of condylar and ramal vertical asymmetry in adolescents with unilateral and bilateral posterior crossbite using cone beam computed tomography (CBCT) - Halicioglu Koray; Celikoglu Mevlut; Yavuz Ibrahim; Sekerci Ahmet Ercan; Buyuk Suleyman Kutalmis (Sciendo, 2014)
Aims: The primary purpose was to evaluate condylar and ramal vertical asymmetry in adolescent patients displaying unilateral posterior (UCB) and bilateral posterior crossbite (BCB) malocclusions. A secondary aim was to compare the findings with a matched control group exhibiting normal occlusion (CG) using cone beam computed tomography (CBCT).